Small population size and possible extirpation of the threatened Malagasy poison frog Mantella cowanii - Edmonds,Devin; Andriantsimanarilafy,Raphali Rodlis; Crottini,Angelica; Dreslik,Michael J.; Newton-Youens,Jade; Ramahefason,Andoniana; Randrianantoandro,Christian Joseph; Andreone,Franco (PeerJ, 2024)
Amphibians are experiencing severe population declines, requiring targeted conservation action for the most threatened species and habitats. Unfortunately, we do not know the basic demographic traits of most species, which hinders population recovery efforts. We studied one of Madagascar’s most threatened frog species, the harlequin mantella (Mantella cowanii), to confirm it is still present at historic localities and estimate annual survival and population sizes. We surveyed eleven of all thirteen known localities and were able to detect the species at eight. Using a naïve estimate of detection probability from sites with confirmed presence, we estimated 1.54 surveys (95% CI [1.10–2.37]) are needed to infer absence with 95% confidence, suggesting the three populations where we did not detect M. cowanii are now extirpated. However, we also report two new populations for the first time. Repeated annual surveys at three sites showed population sizes ranged from 13–137 adults over 3–8 years, with the most intensively surveyed site experiencing a >80% reduction in population size during 2015–2023. Annual adult survival was moderately high (0.529–0.618) and we recaptured five individuals in 2022 and one in 2023 first captured as adults in 2015, revealing the maximum lifespan of the species in nature can reach 9 years and beyond. Our results confirm M. cowanii is characterized by a slower life history pace than other Mantella species, putting it at greater extinction risk. Illegal collection for the international pet trade and continued habitat degradation are the main threats to the species. We recommend conservation efforts continue monitoring M. cowanii populations and reassess the International Union for Conservation of Nature (IUCN) Red List status because the species may be Critically Endangered rather than Endangered based on population size and trends.
Keywords: Amphibian declines; Capture-mark-recapture; Conservation; Demography; Habitat loss; Harlequin mantella; Madagascar; Wildlife trade; Population monitoring; Endangered species